Expressão gênica de células do cumulus e oócitos bovinos sbmetidos à maturação un vitro com diferentes macromoléculas, EGF e Butirolactina I - Souza, Diego Gouvêa de [UNESP] (2014)
The aim of this study was to quantify the abundance of genes associated with the development of oocyte competence in oocytes (GDF-9, BMP15 and OOSP1) and in cumulus cells (GREM1, PTGS2, PFKP, AREG, EREG, HAS2, VCAN, PTX3, ADAM10 and ADAM-17) of immature oocytes (GV), in vivo matured (IVMO) and cultured in IVM medium with different macromolecules (FCS, BSA or PVA), different EGF concentrations or pre-cultured with butyrolactone I (BLI) before IVM. The experimental design consisted of three IVM experiments of bovine oocytes, namely: experiment 1, cumulus-oocyte complex matured in culture medium containing 10% FCS or 1 mg/mL PVA or 4 mg/mL BSA; Experiment 2, cumulus-oocyte complex matured in culture medium containing EGF (at concentrations of 0, 10 and 100 ng/mL); and Experiment 3, cumulus-oocyte complex in vitro matured in the absence (BL0) or presence of pre-maturation with 10 μM de BLI (BL12, 12 hours of pre-maturation and 12 hours of IVM, BL24, 24 hours of pre-maturation and 24 hours of IVM). The relative amount of transcripts for GREM1, PTGS2, PFKP and AREG gene was larger than (P <0.05) in cumulus cells of IVMO oocytes in experiments 1 and 2 and for GREM1 gene in experiment 3. In experiment 1, the FCS group exhibited higher (P <0.05) abundance of transcripts of GREM1 and AREG among MIV groups. In experiment 2, the addition of 10 ng/ml to the IVM medium provided an upregulation of EREG. In experiment 3, BL12 showed higher (P <0.05) abundance of AREG and BL24 of EREG and PTX3. Among IVM groups, the GREM1 gene was expressed in larger quantities (P <0.05) in BL12. There was no statistical difference in experiments 1, 2 and 3 among groups of oocytes IVM, IVMO and GV for GDF9, BMP15 and OOSP1 genes. It was concluded that the use of different macromolecules, different EGF concentrations and the performance of pre-culture with BLI change the transcription in the cumulus cell of genes associated with oocyte competence